THE ECONOMIC DEMONSTRATOR: PREPARE IT ONCE, USE IT MANY TIMES. V. LIQUID–LIQUID PHASE TRANSITION PHENOMENA - M. Bukleski, Vladimir Petruševski (My University, 2019)
A simple and economic way of conducing demonstration experiments about liquid– liquid phase transitions is presented and discussed. Pairs of liquids are sealed in a series of ampoules and each ampoule is put in a beaker filled with either ice or hot water. Depending on the nature of the components mixed, the system can become homogeneous or heterogeneous. Three kinds of systems are discussed: a system with upper critical solution temperature (UCST), with lower critical solution temperature (LCST), and a system with both upper and lower critical solution temperature.
–
Keywords: phase transitions; economic demonstrations; nitrobenzene; hexane; nicotine; triethylamine; Gibbs energy of mixing; demonstrations; physical chemistry